Biomechanical Evaluation of Circumtibial and Transmembranous Routes for Posterior Tibial Tendon Transfer for Dropfoot. (July 2018) - Wagner, Emilio; Wagner, Pablo; Zanolli, Diego; Radkievich, Rubén; Redenz, Gunther; Guzman, Rodrigo
Background: Tibialis posterior tendon transfer is performed when loss of dorsiflexion has to be compensated. We evaluated the circumtibial (CT), above-retinaculum transmembranous (TMAR), and under-retinaculum transmembranous (TMUR) transfer gliding resistance and foot kinematics in a cadaveric foot model during ankle range of motion (ROM). Methods: Eight cadaveric foot-ankle distal tibia specimens were dissected free of soft tissues on the proximal end, applying an equivalent force to 50% of the stance phase to every tendon, except for the Achilles tendon. Dorsiflexion was tested with all of the tibialis posterior tendon transfer methods (CT, TMAR, and TMUR) using a tension tensile machine. A 10-repetition cycle of dorsiflexion and plantarflexion was performed for each transfer. Foot motion and the force needed to achieve dorsiflexion were recorded. Results: The CT transfer showed the highest gliding resistance ( P < .01). Regarding kinematics, all transfers decreased ankle ROM, with the CT transfer being the condition with less dorsiflexion compared with the control group (6.8 vs 15 degrees, P < .05). TMUR transfer did perform better than TMAR with regard to ankle dorsiflexion, but no difference was shown in gliding resistance. The CT produced a supination moment on the forefoot. Conclusion: The CT transfer had the highest tendon gliding resistance, achieved less dorsiflexion and had a supination moment. Clinical Relevance: We suggest that the transmembranous tibialis posterior tendon transfer should be the transfer of choice. The potential bowstringing effect when performing a tibialis posterior tendon transfer subcutaneously (TMAR) could be avoided if the transfer is routed under the retinaculum, without significant compromise of the final function and even with a possible better ankle range of motion.